2020
DOI: 10.3329/bjm.v37i2.51208
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunogenicity and Protective Efficacy of the Intranasal and Intraperitoneal Immunization Routes of <i>Escherichia albertii</i> Strain DM104 in Mouse Model

Abstract: In recent years, our group isolated the Escherichia albertii strain DM104 and characterized it as a vaccine strain against Shigella dysenteriae type 4 in the guinea pig eye model. Protective efficacy of different routes of immunization such as intranasal, oral, and intrarectal routes were also determined and compared by challenging immunized guinea pigs against live S. dysenteriae. In the current study, we compared the intranasal and intraperitoneal routes of immunizations with the DM104 vaccine strain in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The protective immunity provided by the E. albertii strain DM104 in guinea pig model [7,8] and mouse model [9] challenged with S. dysenteriae type 4 was previously reported by our group. In the present study, vaccination of mouse model with E. albertii strain DM104 conferred protection against S. dysenteriae type 4 infection.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The protective immunity provided by the E. albertii strain DM104 in guinea pig model [7,8] and mouse model [9] challenged with S. dysenteriae type 4 was previously reported by our group. In the present study, vaccination of mouse model with E. albertii strain DM104 conferred protection against S. dysenteriae type 4 infection.…”
Section: Discussionsupporting
confidence: 63%
“…In respect of antibody response and protective efficacy, intranasal immunization was found to show promising results. The immunogenicity and protective efficacy of DM104 strain using intranasal and intraperitoneal routes of immunizations were also determined and compared in mouse model against live S. dysenteriae type 4 challenge [9]. In the present study, we evaluated the immunogenicity and protective efficacy of the DM104 strain in orally immunized mice model against S. dysenteriae type 4 challenge and found that the DM104 bacterial strain provided 90% protection and also induced effective mucosal as well as humoral immune response in mice and proved to be a better route of immunization.…”
Section: Introductionmentioning
confidence: 99%